2015
DOI: 10.3892/or.2015.4399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2-methoxyestradiol on apoptosis and HIF-1α and HIF-2α expression in lung cancer cells under normoxia and hypoxia

Abstract: Hypoxic tumor cells are known to be more resistant to conventional chemotherapy and radiation than normoxic cells. However, the effects of 2-methoxyestradiol (2-ME), an anti-angiogenic, antiproliferative and pro-apoptotic drug, on hypoxic lung cancer cells are unknown. The aim of the present study was to compare the effects of 2-ME on cell growth, apoptosis, hypoxia-inducible factor 1α (HIF-1α) and HIF-2α gene and protein expression in A549 cells under normoxic and hypoxic conditions. To establish the optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…To confirm the relationship between HIF‐1α and NDUFA4L2 in lung cancer cells cultured in hypoxia, we used an HIF‐1α inhibitor (2‐ME, 20 μM) and an agonist (DMOG, 1 mM) to pretreat A549 and H1299 cells. DMOG repressed and 2‐ME activated the activation of prolyl hydroxylases and were used to investigate the role of HIF‐1α . First, we confirmed that NDUFA4L2 was located in mitochondria (Fig a).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…To confirm the relationship between HIF‐1α and NDUFA4L2 in lung cancer cells cultured in hypoxia, we used an HIF‐1α inhibitor (2‐ME, 20 μM) and an agonist (DMOG, 1 mM) to pretreat A549 and H1299 cells. DMOG repressed and 2‐ME activated the activation of prolyl hydroxylases and were used to investigate the role of HIF‐1α . First, we confirmed that NDUFA4L2 was located in mitochondria (Fig a).…”
Section: Resultssupporting
confidence: 60%
“…DMOG repressed and 2-ME activated the activation of prolyl hydroxylases and were used to investigate the role of HIF-1α. [25][26][27] First, we confirmed that NDUFA4L2 was located in mitochondria (Fig 2a). Cytochrome C was marked with green, and NDU-FA4L2 was marked with red.…”
Section: Hif-1α Mediated the Survival And Proliferation Of Nsclc Cellsupporting
confidence: 63%
“…2ME is a metabolite of estrogen and has antitumoral activity against many cancer cells, such as lung cancer (9), ovarian cancer (10), hepatocellular carcinoma (11), colon cancer (12) and melanoma (13). Herein, 2ME affected cell lines with different genetic backgrounds, confirming that its effects are independent of BRAF and NRAS mutational status.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Fotsis and collaborators revealed the high cytotoxicity of 2ME in vascular endothelial cells leading to inhibition of tumor angiogenesis and growth in vivo (8). Multiple in vitro and in vivo studies have shown the potential of 2ME to induce cell death and inhibit angiogenesis across many different tumor types (913). In melanoma, the antitumor effect of 2ME has been little explored.…”
Section: Introductionmentioning
confidence: 99%
“…2-ME is a natural endogenous metabolite of 17β-estradiol that exerts anti-proliferative, anti-angiogenic, pro-apoptotic and transcriptional activity in various cells, including induction of cell-cycle arrest (72)(73)(74)(75)(76). Experiments have demonstrated that 2-ME is involved in the inhibi-tion of the polymerization of tubulin in vitro, thus disrupting normal microtubule function (77).…”
Section: Models Of Oxidative Stress and Mitochondrial Dysfunction In mentioning
confidence: 99%